Fin characteristics of aerator devices with lateral deflectors - 吴建华 李丹 马飞 钱尚托 (Journal of hydrodynamics. Series B, 2013)
The fins will be formed if the lateral deflectors in the side-walls with a bottom aerator device are improperly designed, and the flow regime downstream of the aerator device will be worsened. In this paper, the height and the length of the fins induced by the lateral deflectors are theoretically analyzed along with their influencing factors, and the fin characteristics are experimentally investigated on the basis of the theoretical analysis. It is shown that the intensities of the fins are strongly dependent on the ratio of the lateral cavity length to the bottom cavity length, and other factors, like the working head, the height and the angle of the lateral deflector, the flow Froude number around the aerator device, affect the fins indirectly through the changes of the lateral cavity length. When an aerator device with lateral deflectors is designed, it is crucial to match the above mentioned ratio, and to make the ratio of the two cavity lengths less than 1.0 in order to avoid the generation of the fins.